2009
DOI: 10.1002/ange.200902050
|View full text |Cite
|
Sign up to set email alerts
|

Counterion Distribution around Hydrophilic Molecular Macroanions: The Source of the Attractive Force in Self‐Assembly

Abstract: Die Anlagerung von Gegenionen an makroionische {Mo72V30}‐Polyoxometallate nimmt mit steigender Makroionen‐Konzentration und sinkender Solvenspolarität zu. Die Gegenionen verteilen sich im Umkreis von 2–9 Å um das Makroion, mit der höchsten Dichte bei 2–3 Å Entfernung von der Makroionenoberfläche (siehe Bild). Ein enger Zusammenhang zwischen der Anlagerung der Gegenionen und der Selbstorganistion der {Mo72V30}‐Moleküle in brombeerartige Strukturen wird beobachtet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 53 publications
0
22
0
1
Order By: Relevance
“…A simple mean‐field model was developed to qualitatively elucidate the role of bound counterions in the attraction between two like‐charge macroanions, as well as the effect of the dielectric constant of the medium on the interplay between counterion binding and the self‐assembly of the like‐charge macroions. The results from experiment and calculation confirmed that macroion–counterion association is the pivotal contributing source of the attractive forces between the macroanions and, in turn, of their self‐assembly into blackberry structures in solution 32…”
Section: A Retrospective Summary On the Interaction Between Poms Amentioning
confidence: 68%
See 2 more Smart Citations
“…A simple mean‐field model was developed to qualitatively elucidate the role of bound counterions in the attraction between two like‐charge macroanions, as well as the effect of the dielectric constant of the medium on the interplay between counterion binding and the self‐assembly of the like‐charge macroions. The results from experiment and calculation confirmed that macroion–counterion association is the pivotal contributing source of the attractive forces between the macroanions and, in turn, of their self‐assembly into blackberry structures in solution 32…”
Section: A Retrospective Summary On the Interaction Between Poms Amentioning
confidence: 68%
“…Macroanion–counterion interaction plays an important role in blackberry formation. In order to accurately describe the counterion association around macroions and to clarify its relation to the self‐assembly of hydrophilic macroions, SAXS was used to monitor the counterion distribution around 2.5 nm, hollow, spherical POM {Mo 72 V 30 } in water and mixed solvents (acetone/water) 32…”
Section: A Retrospective Summary On the Interaction Between Poms Amentioning
confidence: 99%
See 1 more Smart Citation
“…These results all indicate that the counterions play an important role in this self‐assembly process, in analogy with the self‐assembly of POM macroanions 10. 15 The effective surface charge density of the macroanions is significantly lowered as a result of counterion association, which in turn reduces the repulsion force between two macroanions. In the solution of cationic M 12 L 24 , we believe that the counterion‐mediated attraction is the major driving force for self‐assembly 14.…”
mentioning
confidence: 86%
“…[4c] In particular, counterion distribution around hydrophilic macroanions and selective monovalent cation association and exchange around Keplerate POM macroanions in dilute aqueous solutions are unique and directly related to their self-assembly process. [19] On the other hand, counterions can also affect the behavior of common surfactants in aqueous solution at air/solution interfaces or at solid/solution interfaces and in the micelle-to-vesicle transition processes. [20] Therefore, the effect of counterions on the self-assembly of POM-containing hybrids is an interesting avenue, worth further investigation.…”
Section: Effect Of Counterionsmentioning
confidence: 99%